Bimbingan Teknis Penyelesaian Sengketa Pertanahan dengan Metode Mediasi sebagai Upaya Meningkatkan Kesadaran Hukum Masyarakat - Junaidi Junaidi; Indianto Indianto; Randi Aritama; Mila Surahmi; Desmawaty Romli; Citra Dewi; M. Martindo Merta; Zaimah Husin (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to provide understanding and community empowerment regarding land dispute resolution using mediation methods following laws and regulations to increase public legal awareness in Sirah Pulau Padang District, Ogan Komering Ilir Regency, South Sumatra Province. Implementing this service used technical guidance and interactive discussions—data collection methods through questionnaires, interviews, and observations. Based on the evaluation results, it was found that 50.5% of the participants understood very well, 13.5% understood, 27.2% understood quite well, 5.9% did not understand, and 2.9% did not understand. The results of this service showed that the community's understanding of other options in resolving land conflicts had increased, namely using mediation methods that could save time cost and have a simple process to reach an agreement. Village heads could resolve land conflicts in the community through mediation, following applicable laws and regulations.